Determination of parameters of plane hydrodynamic radiator of acoustic vibrations - Семенець, В.В.; Аврунін, О.Г.; Михайлова, Л.Н.; Косуліна, Н.Г.; Черенков, О.Д. (Radiotekhnika, 2019)
Processing of fibrous materials with aqueous solutions should preserve the natural properties of the fiber in order to obtain high-quality raw materials for the textile industry. This hydrodynamic radiator is a device consisting of a rectangular body with a square tube inside, three conical converging nozzles connected to this tube with slotted outlets. For a theoretical study of a flat hydrodynamic sound emitter, a model of a periodic lattice with a period d formed by a finite number of elastic rods of rectangular cross section is considered. It is assumed that the ends of the bars of the lattice are rigidly fixed, and each rod of the lattice can perform only harmonic elastic bending vibrations. To clarify the design parameters of the transducer, a multifactorial experiment was conducted. As a result of the experiment, the following parameters were established: frequency for washing fibrous materials 1.3 kHz; rod length 26 cm; rod width 4 mm; number of rods 19 pcs .; rod thickness 1.5 mm; grating period 5 mm. A flat hydrodynamic radiator with refined design parameters provides the intensity of sound vibrations within 1.2 W / cm2 on the surface of wool with an oscillating speed of 0.21 m / s. A hydrodynamic emitter should be placed above a layer of fibrous materials at a distance of 7 ∙ 10-3 m.